Negative effects of humor in marketing communications - Baltezarević Ivana; Baltezarević Radoslav (Trendovi u Poslovanju)
Humor is an essential component of human psyche. Smart businesses recognize the value of incorporating humor into their marketing communications. Marketing experts have long recognized that in order to bring their brands closer to their customers, marketing communication must be designed to connect with them emotionally, not just rationally. Because humor captures people's attention, using it into an advertising campaign enables businesses just that, to connect emotionally with their customers. Humor in advertisements is a terrific technique to strengthen companies and elicit favorable emotions in consumers, leaving them with a lasting overall pleasant impression. At the same time, businesses must exercise caution when using humor in their advertising and campaigns. Famous brands have a global presence, and often translate their advertising messages, but this does not always work as planned. Unskillful adaptation of advertising content to foreign markets and misunderstanding of cultural differences can do significant damage to the brand and business in general. Furthermore, if the humor in the advertising message is improper, harsh, or unpleasant, it might elicit negative feelings in customers and provide businesses with the opposite effect than intended. In a digital context, a corporation can enhance brand awareness by creating a creative, hilarious, and viral product promotion that consumers share with their peers. Clumsily created humorous content, on the other hand, is likely to produce consumer unhappiness and trigger negative electronic word of mouth (which is very difficult to control), causing significant damage to brand image and influencing purchasing decisions.